Randomized Phase II Trial of Erlotinib Beyond Progression in Advanced Erlotinib-Responsive Non-Small Cell Lung Cancer. (25th August 2015) - Halmos, Balazs; Pennell, Nathan A.; Fu, Pingfu; Saad, Shumaila; Gadgeel, Shirish; Otterson, Gregory A.; Mekhail, Tarek; Snell, Michael; Kuebler, J. Philip; Sharma, Neelesh; Dowlati, Afshin
Abstract: Background: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) therapy is clearly beneficial in patients with advanced EGFR-mutated non-small cell lung cancer (NSCLC). However, acquired resistance develops uniformly and the benefit of continuation of EGFR TKI therapy beyond progression remains unclear. Materials and Methods: This was a randomized phase II study of chemotherapy (arm A: pemetrexed or docetaxel) versus chemotherapy plus erlotinib (ERL) (arm B) in patients with progressive NSCLC following clinical benefit from erlotinib. In arm B, chemotherapy was given with erlotinib at an oral daily dose of 150 mg on days 2–19 of each cycle to minimize negative pharmacodynamic interactions. The primary endpoint was that continuation of erlotinib in this patient population could extend progression-free survival (PFS) by 50%. Results: A total of 46 patients were randomized (arm A: 24; arm B: 22). Patient characteristics were well balanced except there were more female patients in arm A ( p = .075). The median PFS of patients in arm A was 5.5 months and for those in arm B, 4.4 months ( p = .699). The response rates were 13% and 16% in arms A and B, respectively ( p = .79). EGFR status data were available for 39 of the 46 patients and no significant difference in PFS was seen for continuing ERL beyond progression in mutation-positive patients. Substantially more toxicity was seen in arm B than arm A. Conclusion: There was added toxicity but no benefit with the continuation of ERL beyond progression along with chemotherapy as compared with chemotherapy alone. Implications for Practice: The benefits of continuing erlotinib upon progression alongside conventional chemotherapy are unclear. This randomized phase II study, initiated prior to the establishment of routine epidermal growth factor receptor (EGFR) mutation testing, addressed this clinically relevant issue through randomizing patients with prior clinical benefit from erlotinib (thereby enriching for EGFR-mutated tumors) upon progression in the second- or third-line setting to conventional chemotherapy (single-agent pemetrexed or docetaxel) with or without continued erlotinib. The results showed no benefit to continuing erlotinib beyond progression, while significantly more side effects were noted in the combination arm. Along with other recently presented study findings, these results argue against the routine practice of continuing erlotinib in this setting. Abstract : This was a randomized phase II study of chemotherapy (arm A: pemetrexed or docetaxel) versus chemotherapy plus erlotinib (ERL) (arm B) in 46 patients with progressive non-small cell lung cancer following clinical benefit from ERL. The primary endpoint was that continuation of erlotinib in this patient population could extend progression-free survival (PFS) by 50%. No significant difference in PFS was seen for continuing ERL beyond progression in mutation-positive patients, and patients in arm A experienced more toxicity.